Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan di PT Daeah E&C RDMP Balikpapan - Aznala Trie Wulan Daraizqy; Sofia Ulfa Eka Hadiyanti; Askiah Askiah (MAMEN: Jurnal Manajemen, 2025)
In the digital era, human resources (HR) are a key factor in the success of institutions and companies. Employee performance is significantly influenced by a comfortable and supportive work environment. This study aims to examine the effect of the work environment on employee performance at PT DAEAH E&C RDMP Balikpapan, a construction company that is continuously growing alongside digitalization. The research employs a quantitative method, collecting data through questionnaires distributed to 40 employee respondents. Validity and reliability tests show that the research instruments are valid and reliable. Data analysis using simple linear regression, normality, and heteroscedasticity tests confirm that the regression model is valid and meets statistical assumptions. The results indicate that the work environment has a positive and significant impact on employee performance, with a regression coefficient of 0.842 and a significance value of 0.000 (p < 0.05). A comfortable work environment, good interpersonal relationships, and adequate facilities enhance employee motivation and productivity. This study provides valuable insights for companies to create a conducive work environment that supports improved employee performance. However, the study is limited by the number of respondents and the scope of variables examined, suggesting future research should expand the variables and sample size for more comprehensive results.